Resiliensi Orang Tua dengan Autism Spectrum Disorder (ASD) di SLB Aisyiyah Tulangan Sidoarjo - Sari, Defi Kumala; Mariyati, Ika (ResearchJet Journal of Analysis and Inventions, 2024)
This study aims to describe the characteristics and resilience factors of parent with Autism Spectrum Disorder (ASD) children in SLB Aisyiyah reinforcing sidoarjo. The emerging characteristics and factors that help parents of Autism Spectrum Disorder (ASD) children find strength when facing that their child has Autism Spectrum Disorder (ASD). This research method is qualitative. By using the subject of three pairs of parents of Autism Spectrum Disorder children aged 28-35 years who have problem and have achieved resilience. The date collection method used is the interview method which is equipped with general and field notes. The results of this study indicate that each parent of Autism Spectrum Disorder (ASD) children has the characteristics of insight, independence, relationships, initiative, creativity, humor, morality and has resilience factor I have, I am, I can so that I can rise from adversity. In each subject is also influenced by factors, where the subject has faith and submission to the destiny of Allah SWT. But of the three subject parents of Autism Spectrum Disorder (ASD) children there is a time difference in the resilience process. This is influenced by the support of the closest people, because of Autism Spectrum Disorder (ASD) children need to rise from the problem they are experiencing.